A cation exchange strategy to construct a targeting nanoprobe for enhanced T1-weighted MR imaging of tumors. Issue 37 (19th August 2020) - Chen, Siyu; Zhang, Qin; Sun, Haitao; Zheng, Yingyan; Chen, Qian; Luo, Yu; Chen, Hangrong; Zhou, Quan
Abstract : Excellent imaging performance and good biocompatibility of contrast agents are considered as prerequisites for accurate tumor diagnosis. Abstract : Excellent imaging performance and good biocompatibility of contrast agents are considered as prerequisites for accurate tumor diagnosis. In this study, a novel imaging nanoprobe with actively targeting performance based on ultrasmall paramagnetic iron oxide (USPIO) nanoparticles was constructed by a facile cation exchange strategy followed by conjugation with transferrin (Tf). The stable gadolinium (Gd 3+ ) chelation endows the nanoparticles (NPs) with a low value of r 2 / r 1 (1.28) and a relatively high r 1 value of 3.2 mM −1 s −1, enabling their use for T 1 -weighted positive magnetic resonance (MR) imaging. This constructed transferrin modified gadolinium-iron chelate nanoprobe, named as TUG, shows high biocompatibility within a given dose range. More importantly, compared with clinically used Gd-based small molecule contrast agents, the obtained TUG can be more engulfed by breast cancer cells, showing much enhanced T 1 -weighted positive MR imaging in both subcutaneous and orthotopic tumor models of breast cancer. This novel nanoprobe holds great promise to be utilized as a targeting contrast agent with high efficacy for T 1 -weighted positive MR imaging.